AB0490 Refractory Primary SjÖGren's Syndrome Successfully Treated with Bortezomib. (10th June 2014) - Jakez-Ocampo, J.; Atisha-Fregoso, Y.; Llorente, L.
Abstract : Background: Primary Sjögren's Syndrome (PSS) is a chronic autoimmune disease characterized by sicca complex, systemic manifestations and increased risk of lymphoma. Although it is well accepted the use of steroids for the treatment of systemic manifestations, there is scarce information available regarding the use of targeted therapy for refractory cases. Herein we describe a case of a severe PSS patient refractory to conventional treatment as well as, with a notable response to bortezomib, a proteasome inhibitor commonly used for the treatment of multiple myeloma. Objectives: To describe a clinical case of a patient with refractory PSS successfully treated with bortezomib Methods: A 42 years old woman with a history of 15 years of PSS was evaluated for persistent and refractory hyperglobulinemic purpura and severe fatigue that causes her serious disability. Her globulin levels were 9.6 g/L and the serum viscosity of 3.1 AU, and no response was observed with conventional immunosuppressive therapy namely, prednisone and azathioprine. Initially, the patient received two cycles of rituximab with only partial response in the laboratory parameters. No changes were observed neither in purpuric skin lesions nor in fatigue, even though the globulins level decreased to 3.2 g/L. Considering the persistence of clinical manifestations and of the risk of lymphoma and taking into account the theoretical principle of the activation of B and plasma cells by activation of proteasome in Sjögren's syndrome, the patient received bortezomib (1.3 mg/m 2 ) once a week for two months. The treatment options and her condition at that moment were discussed with the patient who agreed with the therapeutic modality. Results: Bortezomib administration resulted in a notable improvement of general symptoms, a decrease in serum globulin levels from 8.5 to 4.9 g/dL (IgG from 7157 to 3013 mg/dL; IgA from 3069 to 784 mg/dL and IgM from 1353 to 387 mg/dL), as well as in serum viscosity from 3.0 to 2.2 AU. Hyperglobulinemic purpura disappears and prednisone tapering succeeds. After one year of follow-up, the patient is on 7.5 mg/day of prednisone and still without fatigue and skin lesions, although serum globulin levels remain high (4.9 g/dL). Conclusions: As far as we know, this is the first report on the use of bortezomib in a refractory case of PSS. The rationale for its use resembles that of multiple myeloma, where an excessive production of an immunoglobulin by a plasma cell is the characteristic feature of its pathogenesis. Even when PSS is not a hematological neoplasia of plasma cell origin, the hyper viscosity syndrome in our patient were necessarily caused by a B and plasma cell hyperactivity. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5549